The global distribution of Earth's critical zone and its controlling factors - Xianli Xu; Wen Liu (Geophysical Research Letters)
Abstract The near‐surface layer of Earth which provides essential elements for supporting life is now recognized as the critical zone (CZ). This study provides the first global assessment of the CZ thickness (CZT) and its controlling factors by combining data sets of climate, vegetation height (VH), water table depth (WTD), groundwater thickness (GWT), topography, and lithologic data. The analysis shows that CZT ranges from 0.7 to 223.5 m with an average value of 36.8 m across continental areas; CZT is thickest in midlatitudes (subtropical to temperate zones). The proportion of aboveground part (VH) to CZT is 19.9 ± 16.7% (mean ±one standard deviation), while it is 80.1 ± 16.7% for the underground part (WTD + GWT). A generalized linear model shows that compound topographic index (ln(a/tan(b)), where a is the upslope contributing area and b is the slope degree of the landscape) and potential evapotranspiration are the first two major controlling factors on the variations in CZT. This study opens opportunities for further advancing CZ science by providing one of its most important properties—its thickness.